Review on canthin-6-one alkaloids: Distribution, chemical aspects and biological activities - Lea Farouil; Muriel Sylvestre; Alain Fournet; Gerardo Cebrián-Torrejón (European Journal of Medicinal Chemistry Reports, 2022)
Canthin-6-one alkaloids have been a topic of research in many phytochemical and pharmacological laboratories because they are a structurally unique and biologically intriguing family. This review summarizes the diversity, biogenesis, chemistry and bioactivity of canthin-6-ones.